Bone marrow neutrophilia and suppressed bone turnover in human interleukin-6 transgenic mice. A cellular relationship among hematopoietic cells, osteoblasts, and osteoclasts mediated by stromal cells in bone marrow. - Kitamura, H. (1995)
To elucidate the effect of interleukin-6 (IL-6) on bone and bone marrow (BM), human IL-6 transgenic mice (hIL-6 tgm) were produced. Their bone and BM were examined histologically, radiologically, histomorphometrically, and hematologically on a temporal basis. hIL-6 tgm showed histologically evident neutrophilia in BM. Increase in precursors of granulocytes and monocytes in hIL-6 tgm was demonstrated by an assay for colony forming unit in culture (CFU-C) of BM cells. Decrease in osteoblasts and osteoid and suppression of primary spongiosa formation were predominantly observed in hIL-6 tgm at 14 weeks old, the terminal stage of life for hIL-6 tgm. An assay for colony forming unit in fibroblastic (CFU-F) of BM cells revealed a decrease in osteoblast precursor (with regard to alkaline phosphatase-positive colonies) in hIL-6 tgm at 15 weeks old. Histomorphometry demonstrated a decrease of both osteoclast number and bone resorption in hIL-6 tgm. These results suggested that enhanced granulocytic hematopoiesis, suppressed bone turnover, and alteration of cellular population in stromal cells in BM occurred in hIL-6 tgm. Thus we provide new findings that facilitate understanding of cellular interrelationships among hematopoietic cells, osteoblasts, and osteoclasts mediated by stromal cells in BM.